Antioxidant effect of caffeic acid phenethyl ester in experimentally induced periodontitis - DEMİR, ESRA; Otan Ozden, Feyza; Lutfioglu, Muge; Demir, ESRA; Bilgici, Birsen (My University, 2021)
Objectives The aim of the present study was to evaluate the antioxidant effect of systemically administered caffeic acid phenethyl ester (CAPE) in periodontitis. Materials and methods Forty rats were randomly divided into four groups: control, lipopolysaccharide-induced experimental periodontitis (LPS), CAPE 5: LPS+5 mu mol/kg/day CAPE, and CAPE 10: LPS+10 mu mol/kg/day CAPE. Following lipopolysaccharide-induced experimental periodontitis, CAPE was administered intraperitoneally for 28 days. Gingival and serumal total antioxidant status (TAS) and total oxidant status (TOS) were analyzed by enzyme-linked immunosorbent assay (ELISA). Results Gingival tissue TAS was significantly higher with CAPE application compared with the LPS group and was highest in the CAPE 10 group (p0.05). Conclusions The effect of CAPE on increased TAS and decreased TOS levels in inflamed gingival tissue indicates the antioxidant therapeutic potential of CAPE in periodontitis.